Analysis of Mental Workload in The Production Department PT. XYZ Using NASA-TLX Method - Fajri Arinal Haq; Wahyudin Wahyudin; Fatmawati Pratiwi (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
PT. XYZ is a Machining, Fabrication, Automation, Manufacturing (Precision Part, JIG & Fixture) company, Engineering (Design Mechanic, pneumatic, system, Hydraulic System) and maintenance services. Production operators, with limited resources, often carry out large, complex, time-consuming jobs with high demands on quality and accuracy. These conditions make operators often do work that demands more attention in a long period of time, often even working overtime so that work can be completed on the target time. It is feared that what this operator is experiencing will exceed the limits of their workload, especially the amount of mental workload. To analyze this PT. XYZ uses the NASA-TLX (National Aeronautics and Space Administration Task Load Index) method on workers from the production department. The results showed that the mental workload felt by ten workers was included in the high classification with an average WWL value of 76.33. PT. XYZ merupakan perusahaan Machining, Fabrication, Automation, Manufacturing (Precision Part, JIG & Fixture), Engineering (Design Mechanic, pneumatic, system, Hydraulic System) serta jasa maintenance. Operator produksinya, dengan sumber daya yang terbatas, sering melakukan pekerjaan dalam jumlah yang besar, kompleks, waktu yang singkat, serta tuntutan kualitas dan ketelitian yang tinggi. Kondisi tersebut membuat operator sering melakukan pekerjaan yang menuntut perhatian lebih dalam periode waktu yang lama, bahkan sering lembur agar pekerjaan dapat selesai pada terget waktunya. Apa yang dialami operator ini dikhawatirkan akan melebihi batas beban kerjanya, terkhusus besarnya beban kerja mental. Untuk menganalisa hal tersebut PT. XYZ menggunakan metode NASA-TLX (National Aeronautics and Space Administration Task Load Index) pada pekerja dari departemen produksi. Hasil penelitian menunjukkan bahwa beban kerja mental yang dirasakan oleh sepuluh pekerja masuk dalam klasifikasi tinggi dengan nilai WWL rata-rata adalah 76,33.